Transformational leadership and its impact on educational innovation in Ecuador: a systematic review - Román-Cortéz, Kenya Roxana; Cisneros, Juan Tarquino Calderón; Trejo, Carlos Alcívar; Chapín, María Paula Calderon (Frontiers in Education, 2025)
IntroductionThis study explores the impact of transformational leadership on educational innovation in Ecuador. Given the current demand for pedagogical transformation, transformational leadership has emerged as a key driver of innovation through practices such as inspirational motivation and idealized influence. However, existing literature shows gaps in rural applications and long-term assessments.MethodsA systematic review was conducted following PRISMA guidelines, and a bibliometric analysis was performed using the Bibliometrix R-package. Peer-reviewed academic articles published between 2018 and 2024 were retrieved from indexed databases. The inclusion criteria focused on studies examining the relationship between transformational leadership and innovation in educational processes.ResultsFindings reveal a positive correlation between transformational leadership practices-particularly inspirational motivation and idealized influence-and the implementation of educational technologies and disruptive pedagogical methodologies. The review also highlights research gaps, particularly the lack of studies in rural contexts and limited longitudinal evaluations.DiscussionThe results underscore the importance of transformational leadership in fostering innovation in educational settings. Addressing the identified gaps may strengthen leadership strategies and support sustainable development in the education sector. This article offers a comprehensive synthesis that can inform future leadership practices and policymaking in educational institutions.